Pedagogic Competence Of Teachers In The Era Of Society 5.0 Darul Hikmah Islamic Elementary School Makassar City - Irviana, Ira; Usman, Syahruddin; Marjuni, Andi; Syamsudduha, St (Journal of Research and Multidisciplinary, 2024)
This study aims to examine the reality of teachers' pedagogic competence in optimizing student learning in the society 5.0 era and describe the inhibiting factors and supporting the pedagogic competence of teachers of SD Islam Darul Hikmah Makassar. The method used is qualitative descriptive with data collection through observation, interviews and documentation. The research informant used was a teacher of SD Islam Darul Hikmah. The data was analyzed qualitatively using data condensation, data presentation and drawing research conclusions. The results of the study show that: teachers of SD Islam Darul Hikmah Makassar need to have high pedagogic competence to face the challenges and opportunities offered by profound changes in the way of interacting with technology and information. Teachers' pedagogic competencies, including a deep understanding of effective teaching methods, the ability to design technology-based learning, and skills in evaluating and improving student learning, are key factors in improving the quality of education in primary schools. This research has implications for the importance of sustainable competency development for elementary school teachers in Makassar. Teacher training and competency development programs must be held regularly to ensure that teachers remain updated with developments in education and technology.